Perguruan Tinggi Islam dalam Mencetak Generasi Ulul Albab - Fatoni, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2015)
Muslims is majority in the country should gain the education quality .Various amendments and improvements in college islam that should make us are likely to consider another self, and improve quality for improving the qualit y and quantity of islamic education in indonesia. Has been commonly known the presence of indonesian islamic universities in much of change, in line with the progress of knowledge and science and technology .It is time to college graduates who can integrate I slamic religion and science in an al quran with an “ulul albab”. called. Indonesian Islamic universities in a strategic position to get the “ulul albab”.